Use of intraluminal protection in colonic anastomosis in dogs - Oliveira,André Lacerda de Abreu (2007)
PURPOSE: To test the use of intraluminal protection in colonic anastomosis without intestinal cleansing. The intraluminal liner was fashioned from porcine submucosa preserved in glycerin and then fixed 10 cm anteriorly to the anastomotic site. This technique was compared with the one used in termino-terminal colonic anastomosis without intraluminal protection. METHODS: Twenty-eight dogs were divided into two groups of fourteen animals each. Clinical and histopathological tests were performed on the fourth and twenty-first postoperative days. RESULTS: The morbidity and mortality rates were higher in animals that did not receive the intraluminal liner. Histopathological examinations in animals in which the intraluminal liner was used showed better healing, characterized by milder inflammation and increased amount of collagen. CONCLUSION: It can be concluded that the use of intraluminal protection decreases complication rates in colonic anastomosis and promotes better healing.